Renoprotective effects of renin–angiotensin system inhibitor combined with calcium channel blocker or diuretic in hypertensive patients: A PRISMA-compliant meta-analysis. Issue 28 (July 2016) - Cheng, Yiming; Huang, Rongshuang; Kim, Sehee; Zhao, Yuliang; Li, Yi; Fu, Ping
Abstract: Objectives: To conduct a meta-analysis of studies comparing the renoprotective effects of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACEI/ARB) combined with either calcium channel blocker (CCB) or diuretic, but not both, in hypertensive patients. Data sources: Pubmed, Embase, Medline, and Cochrane databases were searched to identify randomized controlled trials (RCTs) of blood pressure lowering treatments in patients with hypertension. Study selection: RCTs comparing the renoprotective effects of ACEI/ARB plus CCB with ACEI/ARB plus diuretic in hypertensive patients, with at least one of the following reported outcomes: urinary protein, estimated glomerular filtration rate/creatinine clearance (eGFR/CrCl), or serum creatinine. Results: Based on 14 RCTs with 18, 125 patients, statistically significant benefits were found in ACEI/ARB plus CCB for maintaining eGFR/CrCl (standardized mean difference [SMD] = 0.36; 95% confidence interval [CI]: 0.20–0.53; P < 0.001), serum creatinine reduction (mean difference [MD] = −0.05 mg/dL; 95% CI: −0.07 to −0.03; P < 0.001). However, no statistical differences were found between the 2 therapeutic strategies in terms of urinary protein (MD = 7.48%; 95% CI: –6.13% to 21.08%; P = 0.28; I 2 = 92%). Conclusions: This meta-analysis concluded that ACEI/ARB plus CCB have a stronger effect on the maintenance of renal function in patients with hypertension than ACEI/ARB plus diuretic.